PENGARUH REKRUTMEN TERHADAP PRESTASI KERJA GURU - NurKafidz Nizam Fahmi; Ainul Aqodah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
The objectives of this study are 1). To find out the recruitment at MTs Al-amiriyyah Blokagung Banyuwangi 2). This is to determine the work performance of teachers at MTs Al-amiriyyah 3). This is to determine the effect of recruitment on teacher work performance at MTs Al-amiriyyah. This type of research is quantitative descriptive using observation, questionnaires, and documentation for data collection techniques, data analysis using the product moment. The population in this study were 42 teachers / educators at MTs Al Amiriyyah. After analyzing the findings, it was found that the implementation of the recruitment was very influential on the work performance of MTs Al Amiriyyah teachers as evidenced by the results of data analysis of 0.662. It can be said that 0.662 <0.312. This means that there is a strong relationship between recruitment and teacher work performance at MTs Al Amiryyah Blokagung Banyuwangi